2011
DOI: 10.1590/s0104-77602011000200006
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic structure in natural populations of Geonoma schottiana Mart (arecaceae): implications for conservation

Abstract: Geonoma schottiana is an underbrush palm which is found in high densities in tropical forests. This species is known for having an asynchronous fruit producing pattern, over all seasons of the year, thus being an important food source for frugivores. This work aims to determine the diversity and spatial genetic structure of two natural populations, referred to as MC I and MC II, of which 60 individuals were sampled, in Poço Bonito Biological Reserve, Lavras, Minas Gerais state. Results of 10 polymorphic isozym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
6
0
4
Order By: Relevance
“…(Eguiarte et al 1992), Geonoma schottiana Mart. (Silva et al 2011), Phoenix dactylifera Linn. (Arabnezhad et al 2012) and Oenocarpus bataua Mart.…”
Section: Discussionmentioning
confidence: 99%
“…(Eguiarte et al 1992), Geonoma schottiana Mart. (Silva et al 2011), Phoenix dactylifera Linn. (Arabnezhad et al 2012) and Oenocarpus bataua Mart.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Silva et al (2011) studying two populations of Geonoma schottiana Mart. (Arecaceae) using isoenzymes, noted the absence of genetic structure in one population, while the other showed a weak and non-significant structure, with the Sp value equal to 0.006.…”
Section: Spatial Genetic Structurementioning
confidence: 99%
“…Other population genetic structure parameters, such as Wright's inbreeding coefficient and gene flow, have shown that, in general, genetic differentiation (F ST ) is low, indicating genetic variation higher within -rather than among -populations and a high gene flow among populations (Elshibli and Korpelainen, 2008;Martins-Corder et al, 2009;Shapcott et al, 2009;Namoff et al, 2011;Silva et al, 2011;Giovino et al, 2014;Nazareno and dos Reis, 2014;Oliveira et al, 2014;Moura et al, 2015). Recently, Ramos et al (2016) found a high level of genetic diversity, mostly within populations, for adults and seedlings in populations of A. aculeatum, and along with results for spatial genetic structure indicated short-distance seed dispersal and modest levels of pollen flow.…”
Section: Introductionmentioning
confidence: 99%